Andrew Lloyd Webber Broadway favorites collection [videorecording (DVD)] - Lloyd Webber, Andrew, 1948- (Universal, 2004)
Audiences around the globe have been captivated by the record-breaking, award-winning productions of Sir Andrew Lloyd Webber, the worlds most successful composer for the stage. The first person to have three musicals running simultaneously in New York and London, Webber helped define the musical theatre genre with the early works in this collection.